Two Children With Steroid-Resistant Significant Proteinuria Due to Nonsense Mutations of the TRIM8 Gene: A Case Report and Literature Review - Li, Xiaojie; Wei, Yaqin; Wang, Meiqiu; Jia, Lili; Shi, Zhuo; Yang, Xiao; Ju, Tao; Kuang, Qianhuining; Xia, Zhengkun; Gao, Chunlin (Frontiers in Pediatrics, 2022)
Background TRIM8 gene mutations have been reported as the genetic basis of autosomal dominant (AD) neuro-renal syndrome in children, which presents with epileptic encephalopathy, focal segmental glomerulosclerosis (FSGS), developmental delay, and mental retardation. In this study, we report the cases of two children with significant proteinuria due to de novo nonsense mutations of the TRIM8 gene. Case Presentation Case 1 was a 7-year-old girl who presented with proteinuria and developmental delay, and her renal biopsy showed FSGS. She developed end-stage renal disease (ESRD) 3 years after onset. Case 2 was another 7-year-old girl who developed proteinuria only at age 3, and renal biopsy showed glomerular segmental mesangial proliferative lesions. The two girls underwent genetic testing but we did not find a positive result in the whole exon. However, cluster analysis revealed two new nonsense mutations of the TRIM8 gene (c.1461C>A, p.Tyr 487* and c.1453C>T, p.Gln485*). Conclusions We reported the clinical manifestation of this neuro-renal syndrome for the first time in China. It is necessary to perform genetic testing in children with steroid-resistant significant proteinuria to identify its etiology and avoid the side effects of immunosuppressants.